Performance characteristics of bipolar Zn/MCM-41/MnO2 Cell - Mohd Zawi, Nor Liza; Othman, Raihan; Ani, Mohd Hanafi; Saputra, Hens (Trans Tech Publications, Switzerland, 2012)
We investigate Zn/MnO2 Leclanché cell employing inorganic MCM-41 membrane separator. MCM-41 membrane is developed onto zinc anode substrate from dip coating procedure, performed at room temperature. The parent solution for synthesis consisted of quarternary ammonium surfactant, cethyltrimethylammonium bromide C16H33(CH3)3NBr (CTAB) as the organic template, sodium hydroxide, deionized water, ethanol and tetraethylorthosilicate (TEOS). Zn/MCM-41/MnO2 cell, about the size of R2025 coin cell, is fabricated both in monopolar and bipolar designs. Bipolar cell configuration enhances the cell performance markedly. The cell demonstrates volumetric energy density - 42 Wh/l for bipolar design and 12 Wh/l for monopolar design, rated at continuous current drain of 1 mA.